Theory of Dimensions and Tires Rolling Resistance - D.H. Valeev (Механика машин, механизмов и материалов, 2008)
Well-known methods of tires rolling resistance definition are observed and analyzed. The results of elaboration of original methods for calculation of force of tires rolling resistance based on experimental data and various factors (tire material, construction, protector type etc.) using the theory of dimensions are presented. Universal analytic algorithm to perform the linear equation of coefficient of tires rolling resistance with critical velocity is elaborated and experimentally tested.